Where Is Islamic Boarding School Research Heading? A Bibliometric Analysis Of Trends In 2014–2024 - Malihah, Lola; Armah; Patimah, Siti (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study employs a bibliometric approach to analyze scientific research trends on Islamic boarding schools (pondok pesantren). Data were collected from Google Scholar using the Publish or Perish software, with the keyword “pondok pesantren” and its variations. The analyzed publication period spans from 2014 to 2024. The inclusion criteria cover relevant scholarly publications written in English and containing complete metadata, while non-scholarly, irrelevant, or incomplete publications were excluded from the analysis. The bibliometric search was conducted using Publish or Perish to extract publication metadata from the Google Scholar database, based on specified keywords and timeframes. The collected data were then analyzed with VOSviewer to visualize bibliometric relationships such as co-authorship, co-citation, and keyword analysis. The findings indicate that the dominant themes in pondok pesantren research include character education as the foundation of moral development for students (santri), adaptive pesantren management in response to contemporary challenges, digitalization in learning and administration, and gender issues concerning the roles and participation of women within pesantren environments.